FORGIVENESS AMONG JAVANESE ETHNIC STUDENTS: A MOUNTAINOUS, HIGHLAND, LOWLAND, AND COASTAL CULTURE BACKGROUND COMPARISON - Nurlatifah, Andar Ifazatul (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2020)
It has been repeatedly documented in the scientific literature that culture plays an important role in forgiveness. However, research of mountainous, highland, lowland and coastal culture related to forgiveness was rare. The goal of this study was to describe the comparison of forgiveness among Javanese ethnic students who had been raised in mountainous, highland, lowland, and coastal culture background. Forgiveness Scale developed to obtain the data was adapted from TRIM and has been tested for its reliability and validity using the Rasch model. Descriptive statistics, Kruskal-Wallis (H) test, and Mann-Whitney (U) posthoc test were used to analyze the data. The result showed an insignificant difference in forgiveness but showed a significant difference in lessen-avoidance motivation. This finding had practical implications in multicultural counselling, especially in promoting forgiveness to various counselees. For a more comprehensive understanding, further research in forgiveness motives is required.